Democratic renewal and the mutual aid legacy of US Mexicans - Pycior, Julie Leininger (Texas A & M University Press, 2014)
The legacy of the historic mutual aid organizing by US Mexicans, with its emphasis on self-help and community solidarity, continues to inform Mexican American activism and subtly influence a number of major US social movements. In Democratic Renewal and the Mutual Aid Legacy of US Mexicans, Julie Leininger Pycior traces the early origins of organizing in the decades following the US-Mexican War, when Mexicans in the Southwest established mutualista associations for their protection. Further, she traces the ways in which these efforts have been invoked by contemporary Latino civil rights leader.